Security against DoS attack in mobile IP communication - Parvin, S.; Ali, S.; Han, Song; Dillon, Tharam S. (ACM, 2009)
As like as wired communication and mobile ad hoc networking, mobile IP communication is also vulnerable to different kinds of attack. Among different kinds of attack Denial-of-Service (DoS) is a great threat for mobile IP communication. In this paper we proposed to imply a lightweight packet filtering technique in different domains and base stations of mobile IP communication. If there is any packet containing spoofed IP address created byDoS attackers, our scheme can detect and then filters the suspected packets. We evaluated the performance of our proposed scheme using ns-2. The results indicate that our proposed scheme can significantly reduce the effect of DoS attacks and improves performance of mobile IP communication.